Organic amendments affect δ13C signature of soil respiration and soil organic C accumulation in a long‐term field experiment in Sweden. (20th August 2013) - Menichetti, L.; Ekblad, A.; Kätterer, T.
Summary: The contribution of young and old soil organic carbon (SOC) pools to soil CO2 fluxes and specific respiration rates of these fluxes was determined by using δ 13 C signatures in the Ultuna long‐term continuous soil organic matter experiment (C‐SOME). Initiated in 1956, the experiment had a range of treatments amended organically and with mineral nitrogen fertilizer under C3 cultivation until 1999, and thereafter under C4 (maize) cultivation. In 2011, soil respiration was measured in situ prior to planting, during growth and after harvest. The contributions from C4 ‐ and C3 ‐C as well as their specific respiration rates were estimated from δ 13 C differences in SOC and CO2 fluxes. The contributions from C4 ‐C sources were further separated into autotrophic and heterotrophic respiration by comparing respiration rates before and after harvest. Between 165 and 385 g C4 ‐C m −2 accumulated during 10 years of maize growth, contributing between 4.9 and 8.1% to the total SOC stock. Although recent C4 ‐C had an average specific respiration rate that was 8.4–22.6 times greater than C3 ‐C, total soil respiration was generally equally split between C3 ‐C and C4 ‐C. Both pools are therefore important sources of CO2 in the overall C budget, and a crucial factor in accounting for SOC stock change caused by management. Experimental treatments influenced specific respiration rates of C4 plant material and accumulation of SOC stock, demonstrating how greater SOC accumulation can be favoured by high‐quality C inputs.